Analysis of Communication in Elastic Optical Networks between Data Centers - Rodrigues, Edson Adriel; Rosario, Denis; Cerqueira, Eduardo; Oliveira, Helder (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2025)
The rapid growth of internet traffic, driven by video streaming, cloud computing, and IoT, is straining traditional optical backbones nearing their capacity limits. Elastic Optical Networks (EONs) address these challenges by enabling dynamic bandwidth allocation with flexible grid technology, improving spectral efficiency. Space-Division Multiplexing (SDM) further enhances capacity through multi-core and multi-mode fibers, offering scalable solutions for future traffic demands. Within Data Center Networks, Elastic Optical Data Center Networks (EODCNs) combine EON and SDM principles to deliver efficient infrastructures capable of supporting the increasing demands of modern digital ecosystems. Our work proposes a routing algorithm for this network model that is capable of enhancing data delivery with an emphasis on satisfying more connections between DCs when compared to other works in the literature.